2008
DOI: 10.1371/journal.pone.0002629
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-4 Controls Intestinal Inflammation by Selective Regulation of Peripheral and Mucosal T Cell Apoptosis and Cell Cycle

Abstract: Galectin-4 is a carbohydrate-binding protein belonging to the galectin family. Here we provide novel evidence that galectin-4 is selectively expressed and secreted by intestinal epithelial cells and binds potently to activated peripheral and mucosal lamina propria T-cells at the CD3 epitope. The carbohydrate-dependent binding of galectin-4 at the CD3 epitope is fully functional and inhibited T cell activation, cycling and expansion. Galectin-4 induced apoptosis of activated peripheral and mucosal lamina propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 40 publications
7
103
0
2
Order By: Relevance
“…Toscano et al demonstrated that systemic treatment of mice with 50 g of galectin-1 per day for 3 days reduced experimental autoimmune uveitis significantly (40), and similar amounts of galectin-9 suppressed allergic asthma (41). However, even higher concentrations of galectin-4 (60 g/day for 8 days) were used to inhibit dextrane sulfate-induced colitis (34). Here we demonstrate that contact allergy can be blocked by i.p.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Toscano et al demonstrated that systemic treatment of mice with 50 g of galectin-1 per day for 3 days reduced experimental autoimmune uveitis significantly (40), and similar amounts of galectin-9 suppressed allergic asthma (41). However, even higher concentrations of galectin-4 (60 g/day for 8 days) were used to inhibit dextrane sulfate-induced colitis (34). Here we demonstrate that contact allergy can be blocked by i.p.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the differences in galectin concentrations required to efficiently block inflammatory disorders might also be attributed to different kinds of administration (e.g., galectin-9 and galectin-1 were injected i.v., whereas galectin-4 and galectin-2 were given i.p. (34,40,41)). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In particular, Gal4 reduces intestinal inflammation by inducing apoptosis of mucosal T cells and reducing pro-inflammatory cytokine secretion (96). However, this lectin was also reported to induce IL-6 production in T cells through PKCϕ-dependent pathways, leading to stimulation of an intestinal inflammatory response (97) (Fig.…”
Section: E Galectin-4 (Gal4)mentioning
confidence: 99%
“…Poor survival Secreted by CRC cells to bind to activated T-cells at the CD3 region, which is translated into a potent inhibition of cell cycle progression and induction of antigen-induced cell death (Paclik et al, 2008) ↑ CA19-9 Poor survival Sialylated Lewis a blood group antigen, secreted in high concentrations into serum of patients with CRC (Yamada et al, 1995) ↑ TSP-1 Poor survival Role in the recruitment, activation and retention of infiltrating T-cells in the lesions of inflammatory diseases.…”
Section: ↑ Galectin-4mentioning
confidence: 99%